Macroeconomic consequences of Covid-19 in a small open economy: an empirical analysis of Nigeria - Oyelami, Lukman O.; Saibu, Olufemi M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
Nigeria is a small open economy with a high level of external dependency especially on the export of crude oil for foreign earnings and government revenue and import of consumables goods including pharmaceutical products. Currently, China and USA contribute more than 35% of Nigerian total import and in addition with Euro area constitute top export destinations of Nigerian crude oil. Studies in the past have investigated the vulnerability of Nigerian economy to external shocks, however, the emerging shocks from global economy due to COVID-19 seems unprecedented. Thus, it is imperative to preemptively examine the likely spillover effects of COVID-19 pandemic to a small open economy like Nigeria based on shocks to strategic trade partners. Given this background, this study investigates the macroeconomic consequences of COVID-19 in China, the Euro area and United States of America (USA) in Nigeria using Global Vector Autoregressive (GVAR) approach. This modelling approach provides an opportunity to analyze international macroeconomic transmission of shocks and spillovers between different countries. It also provides a framework to offer adequate tools to deal with the curse of dimensionality that may arise during the analysis. Macroeconomic variables such as exchange rate, economic growth, inflation rate, trade flows and consumers’ spending were employed from Nigeria and other COVID-19 infected partner countries to build the GVAR model. Similarly, variable such as oil price and world commodity price index served as global variables. These variables were introduced quarterly to obtain stable behavioural interactions. Subsequently, simulations were performed to capture economic reality of COVID-19 and policy reactions in COVID-19 infected partner countries. The study identified output and inflation shocks in USA and China as important external shocks to the Nigerian economy however, oil price shocks constitute the biggest external threat to the economy during and post COVID-19 era.